An investigation into conceptual metaphors in sport commentaries in English versus Vietnamese - Huỳnh Thị Mộng Tuyền (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to find out the similarities and differences of metaphors in football commentaries in English and Vietnamese.